PENGUATAN KEMAMPUAN MEMBACA AL-QUR’AN ANAK MELALUI PROGRAM MAGHRIB MENGAJI ASY-SYIFA - Mifthahul Jannah; Egi Arifin Ilham; Hazral Naufal Al Hilal; Zainal Abidin (Prodi Tadris Ilmu Pengetahuan Sosial FITK UIN Sumatera Utara Medan, 2026)
This study aims to determine the role of the Maghrib Mengaji Asy-Syifa program in improving children's Quran reading skills in the community on Jl. Setia Budi, Gg. Tape, East Helvetia, Medan. This study used qualitative methods with a descriptive approach. Data collection techniques included observation, interviews, and documentation. The study subjects consisted of teachers, students, and several parents involved in the Maghrib Mengaji Asy-Syifa program. The results indicate that the Maghrib Mengaji Asy-Syifa program plays a significant role in improving children's Iqro and Quran reading skills through routine, gradual learning, and the use of repetition. In addition to improving Quran reading skills, this program also positively influences the development of children's morals and religious character, such as politeness and courtesy toward teachers and parents, mutual respect, and a sense of mutual assistance in daily life. Despite several obstacles, the learning process continues to run smoothly through a personal approach and collaboration between teachers and parents. This program serves as a form of community-based Islamic religious education.